The predictability of technical analysis in foreign exchange market using forward return: evidence from developed and emerging currencies - Seri Ghanem; Murad Harasheh; Qays Sbaih; T. K. Ajmal (Cogent Business & Management, 2024)
Technical analysis in the foreign exchange (Forex) market has yielded mixed results, particularly regarding its effectiveness over different holding periods in swing trading. This study addresses this gap by evaluating 497 technical trading rules across 10 currencies over 22 years (January 2000 to December 2022). Focusing on swing trading windows of 1-7 days, the research introduces the concept of an `optimal holding period,' examining how price movements align with trading signals at varying time lags post-signal. The results demonstrate that technical trading rules significantly predict price movements in both developed and emerging market currencies, with emerging markets showing higher levels of predictability. Notably, simple moving average (SMA) indicators perform most effectively for emerging market currencies, while oscillator-based strategies prove more successful for developed markets. These findings have practical implications for Forex traders employing short-term strategies, providing actionable insights for optimizing trade timing. Additionally, the study opens new avenues for future research on the role of technical analysis in enhancing trading performance in global currency markets.
Keywords: 650; Forex; technical analysis; moving averages; Relative strength index; trading signal; holding period